DAMPAK STRATEGI PROMOSI DENGAN MEDIA ONLINE TERHADAP PENYEDIA JASA HOSTING DENGAN STUDI KASUS PADA PASARHOSTING.COM - Aprianto Miduk Pandapotan Saragih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Based on the description that has been stated, a study was conducted to analyze Pasarhosting.com''s online promotion using the Analytical Hierarchy Process (AHP) method entitled